Presos em liberdade : uma análise do regime semiaberto do Sistema Penitenciário de Mato Grosso - Castil, Danielly Brunelly Santos (2022)
This work aims to analyze the criminal execution in the semi-open regime in the Penitentiary System of Mato Grosso, based on John Kingdon's Theory of Multiple Flows, which defends the idea that for an issue to enter the government agenda, the convergence of three flows is necessary. : the recognition of a problem, the identification of a solution or alternatives and the favorable political scenario. In order to do so, we analyze the implementation of criminal enforcement policies specifically for serving sentences in the semi-open regime, in the state of Mato Grosso. The implementation of these policies is a necessary condition for the Penal Execution Law to be fully implemented, seeking to fulfill the functions of the sentence, that is, to prepare the reeducated for the return to social life. To achieve the proposed objectives, a qualitative research was carried out, supported by a literature review, document analysis and semi-structured interview. In the end, we found that the flows, when in convergence, especially in relation to the political flow, tend to enter the government agenda, as in fact happened in the prison system of Mato Grosso from 2020.